Hey Google: Does Environmental Beliefs and Perceived Privacy Risk Influence Potential User’s Intention to Use a Smart Home System in Indonesia? - Elian, Adrian Adhe; Salehudin, Imam (UI Scholars Hub, 2022)
Automation technology has grown in a rapid pace recently. One of the technology that is growing rapidly right now is the Internet of Things or IoT. IoT consist of many devices, and one of the IoT device that are popular right now is called the smart home device. This smart home device can be use to make the house of the user be smart and can be use to save energy for efficiency for the daily life of the user, such as electricity and water that kan provide a negative impact on the environment if used extensively. This smart home device can help to make the energy expense much more efficient. Therefore, this study aims to see and examine the relation between pro-environmental behavior (environmental beliefs and concern), the moderating variable of materialism, perceived privacy risk and trust that can influenced the intention to use of smart home device. This study is an empirical study with quantitative research method. The respondent used in this study is live in Jabodetabek, age above 18 years old, tech savvy, and know the concept of smart home technology but does not have the smart home device. The sample use in this study are 294 samples. The data collected was tested using and analyzed using SEM with LISREL 8.5. The result of the research shows that environmental concern, perceived usefulness, and trust has a positive and significant effect towards intention to use smart home device. For the relationship between environmental beliefs and environmental concern, it was also has positif and significant effect. The result also shown that perceived privacy risk has a negatif significant effect towards trust of smart home device. The result of this research are important for the development of smart home market in Indonesia.